The Effect of Removable Orthodontic Appliances on Oral Microbiota: A Systematic Review - Alessandra Lucchese; Chiara Bonini; Maddalena Noviello; Maria Teresa Lupo Stanghellini; Raffaella Greco; Jacopo Peccatori; Antonella Biella; Elena Tassi; Valeria Beretta; Fabio Ciceri; Marta Marcolina; Enrico Gherlone; et al. (Applied Sciences, 2021)
Background (1): Removable orthodontic appliances may favor plaque accumulation and oral microbe colonization. This might be associated with intraoral adverse effects on enamel or periodontal tissues. The proposed systematic review was carried out to evaluate qualitatively and quantitatively the microbiological changes occurring during orthodontic therapy with removable orthodontic appliances. Methods (2): PubMed, Cochrane Library, Embase, Web of Science, Scopus, Ovid Medline, and Dentistry and Oral Sciences Source were searched. The research included every article published up to January 2020. The Preferred Reporting Items for Reporting Systematic reviews and Meta Analyses (PRISMA) protocol and the “Swedish Council on Technology Assessment in Health Care Criteria for Grading Assessed Studies” (SBU) method were adopted to conduct this systematic review. Results (3): The current study has a moderate evidence, demonstrating that removable appliances do influence the oral microbiota. Significant alterations occur just 15 days after the beginning of therapy, independently from the type of appliance. Furthermore, the levels of oral pathogens decrease significantly or even returned to pre-treatment levels several months later the therapy end. Conclusions (4): This review suggests that orthodontic treatment with removable appliances induces changes to oral microflora, but these alterations might not be permanent.